Penyelesaian Sengketa Ekonomi Adat Minang: Perspektif Hukum Ekonomi Syariah - Yunimar Yunimar (Saqifah: Jurnal Hukum Ekonomi Syariah, 2023)
Abstract, Settlement of customary economic disputes over buying and selling in Minangkabau: Sharia Economic Law Perspective. Resolving business disputes is an important aspect of economic activity in Minangkabau, Indonesia, where the majority of the population adheres to Islam. In this context, The perspective of sharia economic law becomes relevant, considering its focus on Islamic principles in economic transactions. This article discusses the approach to resolving traditional economic disputes between buying and selling in Minang from a sharia economic law perspective, including basic principles, settlement process, and its benefits. By understanding sharia economic law, society and economic actors in Minangkabau can adopt an approach that is more in line with religious values and Islamic business ethics, promote economic justice, and achieve blessings in business. The research method is descriptive qualitative, by conducting surveys and focused group discussions (FGD) to analyze the resolution of business disputes in Minangkabau from the perspective of Sharia Economic Law, Minang people who obey Islamic teachings and are loyal in carrying out customs according to Minangkabau traditional teachings which are based on philosophy“Adat Basandi Syarak, Syarak Basandi Kitabullah”.